96-well plate compatible assay format for screening ankyrin repeat proteins on filter paper - Ryynänen, Vilma (My University, 2025)
In the project our mission was to initiate development of paper-based assay which could replace plastic 96-well plates in recombinant binder protein screening applications. The main aim in the project was to assess cellulose binding domains (CBM) to bind filter papers which can be fused to recombinant binders. The suitability of CBM from Clostridium Thermocellum as anchoring domains for recombinant binder screening on cellulose matrices was studied by fusing an anti-GFP ankyrin repeat domain, called clamp, to the N-terminus of CBM domain. It was confirmed that CBM domain is required for obtaining specific signal from GFP. With coating of 2 μl 200 μg/ml CBM-clamp on filter paper, we demonstrated that GFP signal was saturated at 200 nM concentration and no increase in fluorescence was observed at higher concentrations. Another aspect in the work was to measure whether adding a second CBM in the CBM-clamp fusion would increase the binding affinity, and as a conclusion, it did not improve assay kinetics. Dissociation assay with increased washing steps revealed that CBM binds tightly to cellulose without decrease in signal. However, we found out that the optimal sample volume is 5 μl on filter paper with 3D printed wells because if larger sample volume was used, the CBM was spread beyond the well barrier by capillary flow. Screening of recombinant binders as CBM fusions would decrease plastic waste in research but to reach the point, the assay development requires more research of proper design of fabrication, ways to increase sensitivity, and reproducibility. Keywords: paper-based assay, Cellulose binding domain, assay development, ankyrin repeat protein, 3D printing
Keywords: paper-based assay, Cellulose binding domain, assay development, ankyrin repeat protein, 3D printing